Potential of musa sapientum and imperata cylindrica as an alternative raw material for packaging paper / Muhammad Hadziq Firdaus Mahfidz ...[et al.] - Mahfidz, Muhammad Hadziq Firdaus; Mohd Khairi, Shazaatul Shuhadha; Jemani, Muhammad Afiq Wazini; Muhammad, Arbanah
Until now, most of the pulp and paper production in the world is made from wood plant fibers. Due to the increasing demand in paper industries and shortage of wood origin material in paper-based industries, non-wood fibers have been explored to find the best alternative raw material to produce paper. One of the non-wood fibers that have potential of being raw material in paper-based industries is banana (Musa Sapientum) due to its similar characteristic with wood fiber. Banana fiber has wide range of uses in handicraft industries to make mat, rope and many more. Other than banana fiber, cogon grass (Jmperata Cylindrica) is also an agricultural waste which is capable to be raw material in paper-based industries and hence preventing the environmental problems. Therefore, this study aim to determine the suitability of banana pseudo-stem fiber and cogon grass fiber for packaging paper productions. The method used to make pulp in this study is chemcical pulping using alkali, In conclusion, recent study had proved that banana fiber and cogon grass could be a good potential fiber alternative in paper-based industries in the future. Sample 5 from 80% banana-cogon grass mix fibres showed that it has the highest water absorbency and nearly similar with the reference paper. Sample 5 also showed that it has the highest tensile strength when compared to other samples which can withstand force until 208.044N. The highest elasticity of paper was showed by sample 6 which contain 100% of banana fibre which has the elasticity of 6.603kN/m2. From thermal analysis of paper that was testing by using Differential Scanning Calorimeter, sample 6 showed that it has the highest melting point and hence it reached the minimum requirement to make a good paper which at 81.73 °C. From functional group analysis of paper that was testing by using Fourier Transform Infra-Red (FTIR), all of the sample showed that they have nearly similar peak and functional group of packaging paper.